Tab protection glue in blade battery as well as preparation method and application of tab protection glue

The blade battery ear protection glue prepared by combining polyolefin resin, liquid polybutadiene resin, tackifying resin, anhydride modified wax and toner, solves the problem of poor electrolyte resistance in the prior art, and achieves higher electrolyte resistance and safety.

CN119799203APending Publication Date: 2025-04-11XIAMEN WELDTONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411949817.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The electrolyte resistance of the blade battery ear protective glue is poor, which poses safety risks, especially after adding toner, the performance is further reduced.

Method used

The combination of polyolefin resin, liquid polybutadiene resin, tackifying resin, anhydride modified wax and toner is used to prepare the elbow protective glue by homogenizing and grinding and combining with the melt mixing process.

Benefits of technology

It significantly improves the electrolyte resistance performance of the Electroleum Protective Glue, can maintain stability during long-term exposure to the electrolyte environment, and reduces safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214590890000131
    Figure BDA0005214590890000131
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and particularly relates to tab protection glue in a blade battery as well as a preparation method and application of the tab protection glue. The tab protection glue in the blade battery contains polyolefin resin, liquid polybutadiene resin, tackifying resin, anhydride modified wax, toner and an optional antioxidant, wherein the mass ratio of the polyolefin resin to the liquid polybutadiene resin to the tackifying resin to the anhydride modified wax to the toner is 100: (5-200): (10-450): (5-200): (0.1-150): (0-5). The key point of the invention is that the polyolefin resin, the liquid polybutadiene resin, the tackifying resin, the anhydride modified wax, the toner and the optional antioxidant are matched for use, so that the obtained tab protection glue in the blade battery has excellent electrolyte resistance and can meet the use requirement of soaking in an electrolyte environment for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a tab protection adhesive in a blade battery, and a preparation method and application thereof. Background Art

[0002] As the world pays more attention to renewable energy and electric vehicles, battery technology, as a core component of electric vehicles, has also received more and more attention. Among the many battery technologies, blade batteries have become the focus of the industry with their unique design and excellent performance.

[0003] The blade battery is a lithium-ion battery made of lithium iron phosphate material. Its uniqueness lies in the shape and size of the battery and its production process. The shape of the blade battery is similar to a blade, hence the name. Unlike the winding process of "rolling" together, the blade process in battery manufacturing is to laminate the positive electrode mixture layer, the separator and the negative electrode mixture layer in sequence to form a "sandwich" structure, and then stack multiple "sandwich" structure layers in parallel, and then encapsulate them into the battery shell after stacking in parallel. Now that batteries are becoming more and more popular, the blade process makes it easier to produce large-capacity batteries. In addition, compared with the traditional winding structure, the blade battery has the advantages of more uniform current density, excellent internal heat dissipation performance, and is more suitable for high-power discharge. These characteristics make the blade battery have improved cycle characteristics, safety characteristics and energy density. The uniqueness of the blade battery lies in the design of the pole ears at both ends. This design can make the negative electrode SOC more uniform during charging, thereby reducing the risk of lithium plating.

[0004] The blade battery uses a large-size blade process, so that the battery cell can be directly inserted into the battery pack, eliminating the traditional battery module, thereby improving the energy density and structural strength of the battery pack. However, in the process of assembling the battery cell, such as when inserting the shell, in order to prevent the pole ear from contacting and conducting with the aluminum shell, after the positive and negative electrodes are stacked, a layer of insulating material needs to be attached to the innermost and outermost sides of the pole ear to prevent the inside of the battery cell from contacting the aluminum shell that wraps it, because once it contacts the shell, it will cause a short circuit and make the entire battery cell fail. The insulating material currently used in batteries is mainly tape, but the tape is easily exposed to the electrolyte environment for a long time and falls off. In addition, color powder is often added to the blade battery ear protection glue to give it an identifiable function, so that it can quickly identify whether there is a leak in the scraping process, and at the same time facilitate the identification and inspection of the glue layer after scraping, to meet certain special application scenarios. However, if color powder is added to the blade battery ear protection glue, the electrolyte resistance will be further reduced, and there is a great safety hazard. Summary of the invention

[0005] One of the purposes of the present invention is to provide a blade battery tab protection glue with excellent electrolyte resistance in order to address the defect of poor electrolyte resistance of the blade battery tab protection glue in the prior art.

[0006] The second object of the present invention is to provide a method for preparing the tab protection glue in the above-mentioned blade battery.

[0007] The third object of the present invention is to provide the application of the tab protection glue in the blade battery in protecting the tab of the blade battery.

[0008] Specifically, the tab protection glue in the blade battery provided by the present invention contains polyolefin resin, liquid polybutadiene resin, tackifying resin, anhydride modified wax and color powder and optional antioxidant in a mass ratio of 100:(5-200):(10-450):(5-200):(0.1-150):(0-5).

[0009] The method for preparing the tab protection glue in the blade battery provided by the present invention comprises the following steps:

[0010] S1, homogenizing and grinding the liquid polybutadiene resin and the color powder to obtain a color paste;

[0011] S2, melt-mixing the color paste with the polyolefin resin, the tackifying resin, the anhydride-modified wax and the optional antioxidant.

[0012] The key to the present invention is to use polyolefin resin, liquid polybutadiene resin, tackifying resin, anhydride modified wax and color powder and optional antioxidant in combination, so that the obtained ear protection glue has excellent electrolyte resistance and can meet the use requirements of long-term exposure to electrolyte environment. The reason may be as follows: on the one hand, the stable molecular structure, low solubility and good electrochemical stability of polyolefin resin give it good electrolyte resistance; on the other hand, if the tab protection glue contains color powder, due to the poor dispersion of the color powder in the glue, it is easy to agglomerate into large particles, and the formation of large particles easily leads to stress concentration in the bonding layer and microcracks. These microcracks will become the flow channel of the electrolyte, allowing the electrolyte to flow into the inside of the bonding layer. In this way, the electrolyte will corrode both the surface of the bonding layer and the inside of the bonding layer, greatly reducing the electrolyte resistance of the glue layer. Liquid polybutadiene resin can achieve effective dispersion of the color powder, which can effectively prevent the color powder from agglomerating into large particles in the glue, greatly reducing the risk of microcracks; at the same time, the polar anhydride functional groups in the anhydride-modified wax can form good hydrogen bonds and chemical bonds with the metal substrate (such as copper, aluminum, etc.), and these bonding effects can make the glue layer not easily damaged in an environment corroded by the electrolyte. In summary, the present invention synergistically improves the electrolyte resistance of the tab protection glue from multiple dimensions.

[0013] In a preferred embodiment, the viscosity of the liquid polybutadiene resin at 25° C. is below 3000 mPa·s, which is more conducive to uniform dispersion of the color powder, and the obtained tab protection glue has better electrolyte resistance.

[0014] In a preferred embodiment, the content of the anhydride groups in the anhydride-modified wax is above 1 wt %, which can give the tab protective glue better electrolyte resistance.

[0015] In a preferred embodiment, during the preparation of the tab protective glue in the blade battery, the homogenization and grinding conditions of step S1 are such that the particle size of the obtained color paste is less than 50 μm. At this time, stress concentration caused by excessively large color paste particles can be effectively avoided to cause cracking, thereby giving the tab protective glue better electrolyte resistance. DETAILED DESCRIPTION

[0016] The ear protection glue in the blade battery provided by the present invention contains a polyolefin resin, a liquid polybutadiene resin, a tackifying resin, anhydride-modified wax and a toner and an optional antioxidant in a mass ratio of 100:(5-200):(10-450):(5-200):(0.1-150):(0-5). The mass ratio of the polyolefin resin to the liquid polybutadiene resin is 100:(5-200), such as 100:5, 100:10, 100:20, 100:30, 100:40, 100:50, 100:60, 100:80, 100:100, 100:120, 100:150, 100:180, 100:200 or any value therebetween; the mass ratio of the polyolefin resin to the tackifying resin is 100:( The mass ratio of the polyolefin resin to the anhydride modified wax is 100:(5-200), such as 100:5, 100:10, 100:20, 100:30, 100:40, 100:50, 100:60, 100:80, 100:100, 100:150, 100:200, 100:300, 100:400, 100:450 or any value therebetween; the mass ratio of the polyolefin resin to the anhydride modified wax is 100:(5-200), such as 100:5, 100:10, 100:20, 100:30, 100:400, 100:450 or any value therebetween. 20, 100:30, 100:40, 100:50, 100:60, 100:80, 100:100, 100:150, 100:200 or any value therebetween; the mass ratio of the polyolefin resin to the toner is 100:(0.1-150), such as 100:0.1, 100:0.5, 100:1, 100:5, 100:10, 100:20, 100:30, 100:40, 100:50 , 100:60, 100:80, 100:100, 100:150 or any value therebetween; the mass ratio of the polyolefin resin to the antioxidant is 100:(0-5), such as 100:0, 100:0.01, 100:0.02, 100:0.05, 100:0.1, 100:0.2, 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5 or any value therebetween.

[0017] In the present invention, the content of the polyolefin resin is preferably 10 to 65 parts by weight, such as 10, 15, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65 parts by weight or any value therebetween; the content of the liquid polybutadiene resin is preferably 5 to 18 parts by weight, such as 5, 8, 10, 12, 15, 18 parts by weight or any value therebetween; the content of the tackifying resin is preferably 10 to 45 parts by weight, such as 10, 15, 20, 25, 30, 35, 45 parts by weight or any value therebetween value; the content of the anhydride modified wax is preferably 4.5-20 parts by weight, such as 4.5, 5, 8, 10, 12, 15, 18, 20 parts by weight or any value therebetween; the content of the toner is preferably 0.1-15 parts by weight, such as 0.1, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15 parts by weight or any value therebetween; the content of the antioxidant is preferably 0-0.5 parts by weight, such as 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5 parts by weight or any value therebetween.

[0018] In the present invention, the type and quantity of the polyolefin resin are not particularly limited, and it can be at least one of the homopolymers and copolymers of α-olefins and cycloolefins. Among them, the α-olefin can be listed as at least one of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and 4-methyl-1-pentene. The cycloolefin can be listed as at least one of cyclobutene, cyclopentene and cyclohexene. The polyolefin resin is preferably a compound of two resins with different number average molecular weights, different softening points and different viscosities, which can not only improve the overall fluidity, but also provide sufficient bonding strength and better electrolyte corrosion resistance for the hot melt adhesive. Specifically, the number average molecular weight of the polyolefin resin is preferably 500 to 20000 g / mol, such as 500 g / mol, 1000 g / mol, 5000 g / mol, 10000 g / mol, 15000 g / mol, 20000 g / mol or any value therebetween. The softening point of the polyolefin resin is preferably 70°C to 170°C, such as 70°C, 100°C, 120°C, 150°C, 170°C or any value therebetween.

[0019] In the present invention, the viscosity of the liquid polybutadiene resin at 25° C. is preferably 3000 mpa·s or less, more preferably 100 to 3000 mpa·s, and specifically can be 100 mpa·s, 200 mpa·s, 300 mpa·s, 500 mpa·s, 1000 mpa·s, 2000 mpa·s, 3000 mpa·s or any value therebetween. When the viscosity of the liquid polybutadiene resin at 25° C. is preferably 3000 mpa·s or less, it is more conducive to uniform dispersion of the color powder, and can give the tab protective glue better electrolyte resistance.

[0020] In the present invention, the tackifying resin is conducive to making the hot melt adhesive have suitable viscosity and fluidity, reducing the difficulty of operation when using the hot melt adhesive, and assisting the dispersion of the color powder while ensuring that the ear protection adhesive has good bonding ability. Specifically, specific examples of the tackifying resin include but are not limited to: at least one of C5 petroleum resin, C9 petroleum resin, dicyclopentadiene DCPD resin, coumarone-indene resin, styrene series resin, condensation resin, hydrocarbon petroleum resin and hydrogenated petroleum resin. In addition, the softening point of the tackifying resin is preferably 100°C to 160°C, such as 100°C, 110°C, 120°C, 130°C, 160°C or any value therebetween.

[0021] In the present invention, the anhydride-modified wax can be anhydride-modified polyethylene wax, anhydride-modified polypropylene wax, or a mixture of the two. In addition, the content of anhydride groups in the anhydride-modified wax is preferably 1wt% or more, more preferably 1-10wt%, in which case the obtained ear protection glue has better electrolyte resistance. The content of anhydride groups in the anhydride-modified wax can be, for example, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt% or any value therebetween.

[0022] In the present invention, the toner may be at least one of insulating carbon black, copper manganese black, iron chrome black, ultramarine blue, phthalocyanine blue, iron blue, phthalocyanine green, and iron green.

[0023] In the present invention, specific examples of the antioxidant include, but are not limited to, at least one of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-methylphenol and tris[2,4-di-tert-butylphenyl]phosphite.

[0024] The method for preparing the tab protection glue in the blade battery provided by the present invention comprises the following steps:

[0025] S1, homogenizing and grinding the liquid polybutadiene resin and the color powder to obtain a color paste;

[0026] S2, melt-mixing the color paste with the polyolefin resin, the tackifying resin, the anhydride-modified wax and the optional antioxidant.

[0027] In the present invention, in step S1, the conditions for homogenization and grinding are preferably such that the particle size of the obtained color paste is less than 50μm, for example, 50μm, 48μm, 45μm, 42μm, 40μm, 38μm, 35μm, 32μm, 30μm, 28μm, 25μm, 23μm, 20μm, 18μm, 15μm, 12μm, 10μm, 8μm, 5μm or any value therebetween. At this time, the glue layer can be better prevented from cracking due to stress concentration caused by excessively large color paste particles, thereby giving the tab protection glue better electrolyte resistance. Specifically, the homogenizing conditions preferably include a rotation speed of 800 to 2000 rpm / min, such as 800 rpm / min, 1000 rpm / min, 1200 rpm / min, 1500 rpm / min, 2000 rpm / min, 2500 rpm / min or any value therebetween; a time of 1 to 10 min, such as 1 min, 3 min, 5 min, 7 min, 10 min or any value therebetween. In addition, the grinding can be performed in a three-roll mill. The grinding conditions preferably include a grinding speed of 5 to 20 rpm / min, such as 5 rpm / min, 8 rpm / min, 10 rpm / min, 15 rpm / min, 20 rpm / min or any value therebetween; a time of 1 to 30 min, such as 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min or any value therebetween.

[0028] In the present invention, in step S2, the melt mixing method preferably includes preheating the color paste with the polyolefin resin, the tackifying resin, the anhydride modified wax and the optional antioxidant, and starting to stir and mix until most of the materials are melted until the materials are completely melted. Wherein, the preheating conditions preferably include a temperature of 160 to 230°C, such as 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or any value therebetween; a time of 20 to 30 minutes, such as 20 minutes, 22 minutes, 25 minutes, 28 minutes, 30 minutes or any value therebetween. The stirring and mixing conditions preferably include a temperature of 160-230°C, such as 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or any value therebetween; a stirring speed of 300-500rpm, such as 300rpm, 350rpm, 400rpm, 450rpm, 500rpm or any value therebetween; and a time of 1-5h, such as 1h, 1.5h, 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.5h, 5h or any value therebetween.

[0029] The present invention will be described in detail below through specific embodiments.

[0030] The raw material parts involved in the following examples and comparative examples are all parts by weight.

[0031] Example 1 Tab protection glue in blade battery and preparation method thereof

[0032] S1. 10 parts of liquid polybutadiene resin (Ricon 130 of Cray Valley, with a viscosity of 750 mPa·s at 25° C.) and 5 parts of color powder (Cabot MOGUL L) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 45 μm to 50 μm to obtain a color paste;

[0033] S2, the color paste was mixed with 40 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 30 parts of tackifying resin (Escorez TM 5300), 14.8 parts of anhydride modified polypropylene wax (Licocene pp MA 6452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0034] Example 2 Tab protection glue in blade battery and preparation method thereof

[0035] S1. 10 parts of liquid polybutadiene resin (Ricon 131 of Cray Valley, viscosity of 2750 mPa·s at 25°C) and 5 parts of color powder (Holiday 5008) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 40 μm to 48 μm to obtain a color paste;

[0036] S2, the color paste was mixed with 20 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 20 parts of polyolefin resin (VESTOPLAST 751 from Evonik, Germany), 30 parts of tackifying resin (Escorez from ExxonMobil) TM 5320), 14.8 parts of anhydride modified polypropylene wax (Licocene pp MA 7452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0037] Example 3: Tab protection glue in blade battery and preparation method thereof

[0038] S1. 10 parts of liquid polybutadiene resin (Ricon 156 of Crayville, viscosity of 1600 mPa·s at 25° C.) and 5 parts of color powder (Hai Lijing D7110F) were mixed evenly with a homogenizer, and the obtained mixture was ground with a three-roll mill to a particle size of 40 μm to 45 μm to obtain a color paste;

[0039] S2. Preheat the color paste with 40 parts of polyolefin resin (VESTOPLAST 608 from Evonik, Germany), 30 parts of tackifying resin (Eastotac H-100W from Eastman), 14.8 parts of anhydride-modified polypropylene wax (Licocene pp MA 6452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 at 180°C for 25 minutes. After most of the materials are melted, stir at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0040] Example 4: Tab protection glue in blade battery and preparation method thereof

[0041] S1. 15 parts of liquid polybutadiene resin (Ricon 130 of Cray Valley, with a viscosity of 750 mPa·s at 25° C.) and 10 parts of color powder (Cabot MOGUL L) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 43 μm to 50 μm to obtain a color paste;

[0042] S2, the color paste was mixed with 45 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 18 parts of tackifying resin (Escorez TM 5300), 11.8 parts of anhydride modified polypropylene wax (Licocene pp MA 6452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0043] Example 5 Tab protection glue in blade battery and preparation method thereof

[0044] S1. 15 parts of liquid polybutadiene resin (Ricon 131 of Cray Valley, viscosity of 2750 mPa·s at 25° C.) and 10 parts of color powder (Holiday 5008) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 43 μm to 48 μm to obtain a color paste;

[0045] S2, the color paste was mixed with 25 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 20 parts of polyolefin resin (VESTOPLAST 751 from Evonik, Germany), 18 parts of tackifying resin (Escorez from ExxonMobil), TM 5300), 11.8 parts of anhydride modified polypropylene wax (Licocene pp MA 7452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0046] Example 6: Tab protection glue in blade battery and preparation method thereof

[0047] S1. 15 parts of liquid polybutadiene resin (Ricon 156 of Crayville, viscosity of 1600 mPa·s at 25° C.) and 10 parts of color powder (Hai Lijing D7110F) were mixed evenly with a homogenizer, and the obtained mixture was ground with a three-roll mill to a particle size of 41 μm to 47 μm to obtain a color paste;

[0048] S2. Preheat the color paste with 20 parts of polyolefin resin (VESTOPLAST 751 from Evonik, Germany), 25 parts of polyolefin resin (VESTOPLAST 608 from Evonik, Germany), 18 parts of tackifying resin (Eastotac H-100W from Eastman), 11.8 parts of anhydride-modified polypropylene wax (Licocene pp MA 7452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 at 180°C for 25 minutes. After most of the materials are melted, stir at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0049] Example 7 Tab protection glue in blade battery and preparation method thereof

[0050] S1. 18 parts of liquid polybutadiene resin (Ricon 130 of Cray Valley, with a viscosity of 750 mPa·s at 25° C.) and 12 parts of color powder (Cabot MOGUL L) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 42 μm to 49 μm to obtain a color paste;

[0051] S2, the color paste was mixed with 50 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 15 parts of tackifying resin (Escorez TM 5300), 4.8 parts of anhydride modified polypropylene wax (Licocene pp MA 6452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0052] Example 8 Tab protection glue in blade battery and preparation method thereof

[0053] S1. 18 parts of liquid polybutadiene resin (Ricon 131 of Cray Valley, with a viscosity of 2750 mPa·s at 25° C.) and 12 parts of color powder (Holiday 5008) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 39 μm to 46 μm to obtain a color paste;

[0054] S2, the color paste was mixed with 30 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 20 parts of polyolefin resin (VESTOPLAST 751 from Evonik, Germany), 15 parts of tackifying resin (Escorez from ExxonMobil) and 10 parts of tackifying resin (VESTOPLAST 704 from Evonik, Germany). TM 5320), 4.8 parts of anhydride modified polypropylene wax (Licocene pp MA 7452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0055] Example 9: Tab protection glue in blade battery and preparation method thereof

[0056] S1. 18 parts of liquid polybutadiene resin (Ricon 156 of Crayville, viscosity of 1600 mPa·s at 25° C.) and 12 parts of color powder (Hai Lijing D7110F) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 38 μm to 47 μm to obtain a color paste;

[0057] S3, the color paste was mixed with 20 parts of polyolefin resin (VESTOPLAST 751 from Evonik, Germany), 20 parts of polyolefin resin (VESTOPLAST 608 from Evonik, Germany), 15 parts of tackifying resin (Escorez from ExxonMobil) and 10 parts of tackifying resin (Escorez from ExxonMobil). TM 5320), 4.8 parts of anhydride modified polypropylene wax (Licocene pp MA 6452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0058] Example 10 Tab protection glue in blade battery and preparation method thereof

[0059] S1. 12 parts of liquid polybutadiene resin (Ricon 156 of Cray Valley, viscosity of 1600 mPa·s at 25° C.) and 8 parts of color powder (Cabot MOGUL L) were mixed uniformly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 36 μm to 41 μm to obtain a color paste;

[0060] S2, the color paste was mixed with 50 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 20 parts of tackifying resin (Escorez TM 5300), 4.8 parts of anhydride modified polypropylene wax (Licocene pp MA 6452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0061] Example 11 Tab protection glue in blade battery and preparation method thereof

[0062] S1. 12 parts of liquid polybutadiene resin (Ricon 131 of Cray Valley, viscosity of 2750 mPa·s at 25°C) and 8 parts of color powder (Holiday 5008) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 40 μm to 45 μm to obtain a color paste;

[0063] S2, the color paste was mixed with 50 parts of polyolefin resin (VESTOPLAST 608 from Evonik, Germany), 20 parts of tackifying resin (Escorez TM 5320), 4.8 parts of anhydride modified polypropylene wax (Licocene pp MA 7452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 are preheated at 180°C for 25 minutes. After most of the materials are melted, they are stirred at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0064] Example 12 Tab protection glue in blade battery and preparation method thereof

[0065] S1. 12 parts of liquid polybutadiene resin (Ricon 156 of Crayville, viscosity of 1600 mPa·s at 25° C.) and 8 parts of color powder (Hai Lijing D7110F) were mixed evenly with a homogenizer, and the resulting mixture was ground with a three-roll mill to a particle size of 39 μm to 44 μm to obtain a color paste;

[0066] S2. Preheat the color paste with 25 parts of polyolefin resin (VESTOPLAST 704 from Evonik, Germany), 25 parts of polyolefin resin (VESTOPLAST 608 from Evonik, Germany), 25 parts of tackifying resin (Eastotac H-100W from Eastman), 4.8 parts of anhydride-modified polypropylene wax (Licocene pp MA 7452 from Klein, with anhydride group content of 7wt%), 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irgafos 168 at 180°C for 25 minutes. After most of the materials are melted, stir at 180°C at a speed of 300 rpm for 3 hours. At this time, the materials are completely melted and mixed evenly to obtain the ear protection glue for the blade battery.

[0067] Example 13: Tab protection glue in blade battery and preparation method thereof

[0068] The tab protection glue for blade batteries was prepared according to the method of Example 1, except that the liquid polybutadiene resin was replaced by the same weight portion of non-preferred liquid polybutadiene resin (purchased from Cray Valley Company, brand Ricon 157, viscosity at 25°C was 6000 mPa·s). The remaining conditions were the same as in Example 1 to obtain the tab protection glue for blade batteries.

[0069] Example 14: Tab protection glue in blade battery and preparation method thereof

[0070] The tab protection glue for blade batteries is prepared according to the method of Example 1, except that in step S1, the mixture of liquid polybutadiene resin and color powder is ground to a particle size of 70 μm to 76 μm using a three-roll grinder, and the remaining conditions are the same as in Example 1 to obtain the tab protection glue for blade batteries.

[0071] Comparative Example 1: Tab protection glue in blade battery and preparation method thereof

[0072] The tab protection glue for blade batteries was prepared according to the method of Example 1, except that the liquid polybutadiene resin Ricon 130 was replaced by the same weight portion of polyisobutylene rubber (purchased from BASF, brand B10), and the other conditions were the same as in Example 1 to obtain the tab protection glue for blade batteries.

[0073] Comparative Example 2: Tab protection glue in blade battery and preparation method thereof

[0074] The tab protection glue for blade batteries was prepared according to the method of Example 1, except that the liquid polybutadiene resin Ricon 130 was replaced by the same weight portion of mineral oil (purchased from Karamay Company, brand KN4010), and the other conditions were the same as in Example 1 to obtain the tab protection glue for blade batteries.

[0075] Comparative Example 3: Tab protection glue in blade battery and preparation method thereof

[0076] The tab protection glue for blade batteries was prepared according to the method of Example 1, except that Licocene pp MA6452 was replaced by the same weight portion of non-anhydride modified wax (Licocene pp 6102 from Klein), and the other conditions were the same as in Example 1 to obtain the tab protection glue for blade batteries.

[0077] Test Case

[0078] (1) Viscosity: The tab protection adhesives obtained in the above examples and comparative examples were tested using a BROOKFIELD viscometer. 20 g of hot melt adhesive was placed in a heating sleeve and melted at 180° C. After the temperature stabilized, a No. 27 rotor was used to measure the viscosity at a speed of 10 rpm. The results are shown in Table 1.

[0079] (2) Surface drying time: The tab protection glue obtained in the above examples and comparative examples was dispensed onto the aluminum substrate at a temperature of 180°C, with a glue amount of 0.3 g ± 0.05 g, and tested by finger touch method, i.e., the time from finger touch until the glue is no longer sticky is recorded as the surface drying time. The results are shown in Table 1.

[0080] (3) Shear strength: First, preheat the 3-series aluminum substrate on a 180°C heating platform for 5 minutes, set the dispensing temperature to 180°C, quickly take the preheated substrate for dispensing, control the bonding area to 25.4mm*12.7mm, and the glue thickness to 0.15mm (controlled by copper wire). Then quickly overlap it with another preheated 3-series aluminum substrate on the overlap fixture, and finally clamp it with a dovetail clamp to prepare the sample, 5cps per group. Place the prepared sample in a constant temperature and humidity room (25°C / 55%RH) and let it stand for 24 hours. Then clamp the sample that has been cured for 24 hours on a tensile testing machine for a shear test, with a tensile rate of 10mm / min. The results are shown in Table 1.

[0081] (4) Young's modulus: At 180°C, apply the glue onto the release paper, then quickly transfer the release paper to a 180°C heating platform and use a film scraper to scrape the film to control the film thickness to 0.3 mm. Place the prepared film in a constant temperature and humidity room (25°C / 55% RH) for 24 hours, then cut the cured film into a dumbbell shape, clamp it on a tensile testing machine for tensile testing, and record the Young's modulus data. The results are shown in Table 1.

[0082] (5) Tensile strength: At 180°C, apply glue to the release paper, then quickly transfer the release paper to a 180°C heating platform and use a film scraper to scrape the film to control the film thickness to 0.3 mm. Place the prepared film in a constant temperature and humidity room (25°C / 55% RH) for 24 hours, then cut the cured film into a dumbbell shape, clamp it on a tensile testing machine for tensile testing, and record the tensile strength data. The results are shown in Table 1.

[0083] (6) Elongation at break: At 180°C, apply the glue onto the release paper, then quickly transfer the release paper to a 180°C heating platform and use a film scraper to scrape the film to control the film thickness to 0.3 mm. Place the prepared film in a constant temperature and humidity room (25°C / 55% RH) for 24 hours, then cut the cured film into a dumbbell shape, clamp it on a tensile testing machine for tensile testing, and record the elongation at break data. The results are shown in Table 1.

[0084] (7) Electrolyte resistance: Using aluminum foil as the substrate, a 10 mm × 40 mm × 30 μm strip was scraped out on the substrate at 180°C using a scraping device. After standing at room temperature for 24 hours, the strip was immersed in the electrolyte and immersed at room temperature for 72 hours and 168 hours to observe the shedding condition. The results are shown in Table 1.

[0085]

[0086] It can be seen from the test results in Table 1 that the tab protection glue in the blade battery provided by the present invention has low viscosity, short surface drying time, high bonding strength, and is suitable for scraping and gluing by scraping glue. At the same time, it does not fall off at all after being soaked in the electrolyte for 72 hours, and does not fall off or only partially falls off after being soaked for 168 hours, which shows that it also has excellent electrolyte resistance and can achieve insulation protection for the tab. From the comparison between Example 1 and Example 13, it can be seen that when the viscosity of the liquid polybutadiene resin is controlled within the preferred range, the electrolyte resistance of the obtained tab protection glue is better. From the comparison between Example 1 and Example 14, it can be seen that in the preparation process of the tab protection glue in the blade battery, when the particle size of the color paste is controlled within the preferred range, the tab protection glue can be given better electrolyte resistance, which can meet the use requirements of longer-term exposure to the electrolyte environment, and the application prospects are broader.

[0087] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A blade battery ear protection glue, characterized in that: The tab protection glue in the blade battery contains polyolefin resin, liquid polybutadiene resin, tackifying resin, anhydride modified wax and color powder and an optional antioxidant in a mass ratio of 100:(5-200):(10-450):(5-200):(0.1-150):(0-5).

2. The blade battery tab protection glue according to claim 1, characterized in that: The content of the polyolefin resin is 10 to 65 parts by weight, the content of the liquid polybutadiene resin is 5 to 18 parts by weight, the content of the tackifying resin is 10 to 45 parts by weight, the content of the anhydride modified wax is 4.5 to 20 parts by weight, the content of the color powder is 0.1 to 15 parts by weight, and the antioxidant is 0 to 0.5 parts by weight.

3. The tab protection glue for blade batteries according to claim 1, characterized in that: The polyolefin resin is at least one of a homopolymer and a copolymer of an α-olefin and a cycloolefin; Preferably, the α-olefin is selected from at least one of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and 4-methyl-1-pentene; Preferably, the cycloolefin is selected from at least one of cyclobutene, cyclopentene and cyclohexene; Preferably, the number average molecular weight of the polyolefin resin is 500 to 20000 g / mol; Preferably, the softening point of the polyolefin resin is 70°C to 170°C.

4. The blade battery tab protection glue according to claim 1, characterized in that: The viscosity of the liquid polybutadiene resin at 25° C. is less than 3000 mpa·s.

5. The tab protection glue for blade batteries according to claim 1, characterized in that: The tackifying resin is selected from at least one of C5 petroleum resin, C9 petroleum resin, dicyclopentadiene DCPD resin, coumarone-indene resin, styrene series resin, condensation resin, hydrocarbon petroleum resin and hydrogenated petroleum resin.

6. The tab protection glue for blade batteries according to claim 1, characterized in that: The anhydride-modified wax is anhydride-modified polyethylene wax and / or anhydride-modified polypropylene wax; the content of anhydride groups in the anhydride-modified wax is more than 1 wt%; The toner is selected from at least one of insulating carbon black, copper manganese black, iron chrome black, ultramarine, phthalocyanine blue, iron blue, phthalocyanine green and iron green; The antioxidant is at least one selected from pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-methylphenol and tris[2,4-di-tert-butylphenyl]phosphite.

7. The method for preparing the tab protection glue in the blade battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: S1, homogenizing and grinding the liquid polybutadiene resin and the color powder to obtain a color paste; S2, melt-mixing the color paste with the polyolefin resin, the tackifying resin, the anhydride-modified wax and the optional antioxidant.

8. The method for preparing the tab protection glue in the blade battery according to claim 7, characterized in that: In step S1, the homogenization and grinding conditions are such that the particle size of the obtained color paste is less than 50 μm.

9. The method for preparing the tab protection glue in the blade battery according to claim 7, characterized in that: In step S2, the melt mixing method includes preheating the color paste with the polyolefin resin, the tackifying resin, the anhydride-modified wax and the optional antioxidant, and stirring and mixing after most of the materials are melted until the materials are completely melted; Preferably, the preheating conditions include a temperature of 160 to 230° C. and a time of 20 to 30 min; Preferably, the stirring and mixing conditions include a temperature of 160 to 230° C., a stirring speed of 300 to 500 rpm, and a time of 1 to 5 hours.

10. Use of the tab protection glue in blade batteries as described in any one of claims 1 to 6 in protecting tabs of blade batteries.